PROBLEMATIKA TRANSISI DARI KURIKULUM 2013 MENUJU KURIKULUM MERDEKA - Khotami, Abdul Latif; Faruq, Dukan Jauhari (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The COVID-19 pandemic significantly impacted Indonesia's education system, prompting the transition from the 2013 Curriculum to the Independent Curriculum as part of a learning crisis recovery effort. This study examines various challenges during the transition, focusing on teacher readiness, educational infrastructure distribution, and project-based learning implementation. Using a descriptive qualitative approach, data were collected through interviews, observations, and literature reviews. Findings reveal that the lack of teacher training is a major obstacle, hindering their understanding of the Independent Curriculum’s concepts and methods. Furthermore, the uneven distribution of curriculum textbooks forces schools to rely on less relevant materials. Data were collected through interviews and observations at MI Ma’arif NU 09 Keting, Jember, which has implemented the Independent Curriculum in Grades 1 and 4. The study highlights the importance of continuous teacher training and improved infrastructure distribution to effectively support curriculum implementation. Synergy among policymakers, teachers, and communities is also vital to addressing post-pandemic educational challenges. This research is expected to serve as a reference for improving the education system to sustain the Independent Curriculum.